2019
DOI: 10.3389/fimmu.2019.00881
|View full text |Cite
|
Sign up to set email alerts
|

Scurfy Mice Develop Features of Connective Tissue Disease Overlap Syndrome and Mixed Connective Tissue Disease in the Absence of Regulatory T Cells

Abstract: Due to a missense mutation in the Foxp3 gene, scurfy mice are deficient in functional regulatory T cells (Treg). The consequent loss of peripheral tolerance manifests itself by fatal autoimmune mediated multi-organ disease. Previous studies have outlined the systemic inflammatory disease and demonstrated production of anti-nuclear antibodies (ANA) in scurfy mice. However, specific autoantibody targets remained to be defined. ANA are immunological markers for several connective tissue dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Similar to other Treg‐deficient models, we found that germline DKO mice develop high titer autoantibodies directed against both nuclear and cytosolic antigens with complete penetrance before 4 weeks of age 16,85‐87 . However, despite rescue of Treg, tolerance is not restored in DKO:WT chimeras; rather, we observed development of autoantibodies in all DKO:WT chimeras (but not control WT:WT chimeras), albeit directed exclusively against nuclear autoantigens 16 .…”
Section: Roles Of Nr4a Family In T Cells and The Problem Of Redundancysupporting
confidence: 83%
“…Similar to other Treg‐deficient models, we found that germline DKO mice develop high titer autoantibodies directed against both nuclear and cytosolic antigens with complete penetrance before 4 weeks of age 16,85‐87 . However, despite rescue of Treg, tolerance is not restored in DKO:WT chimeras; rather, we observed development of autoantibodies in all DKO:WT chimeras (but not control WT:WT chimeras), albeit directed exclusively against nuclear autoantigens 16 .…”
Section: Roles Of Nr4a Family In T Cells and The Problem Of Redundancysupporting
confidence: 83%
“…Some published studies also reveal the clues of GEMIN genes and immune cells. In the absence of regulatory T cells in scurfy mice, the myopathy-specific autoantibody profile revealed significantly increased the levels of anti-SMN as well as anti-Gemin3 antibodies in scurfy sera [ 27 ]. Gao et al identified GEMIN3 (rs197412) which was independently associated with overall survival in non-Hodgkin's lymphoma patients, and the prognostic value of GEMIN3 in patient outcomes was also observed in the diffuse large B-cell lymphoma and T-cell lymphoma non-Hodgkin's lymphoma subtypes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples taken from scurfy and WT mice at day 21 of life were assessed for the presence of ANA by an IFA, as previously described ( 10 ). Briefly, sera were diluted in PBS with 0.2% Tween 20 (Roth, Karlsruhe, Germany) and were added to slides precoated with human epithelial cells (HEp-20-10) and primate liver tissue (Euroimmun, Lübeck, Germany).…”
Section: Methodsmentioning
confidence: 99%